(untitled) (Biological Sciences - PJSIR, 1999)
Poly(butylacrylate) wasgraftcopolymerised ontoCaseininthepresenceofphosphate bufferusingpotassium persulphate ascatalyst. The effects ofconcentration ofmonomers, backbone andcatalyst onrateofconversion ofmonomer (Rp), rate ofgraftcopolymerization (Rg),rateofhomopolymerization(Rh),graftingefficiency(OE)andgraftingratio(OR)havebeen discussed.